The burden of Gastric Cancer and possible risk factors from 1990 to 2021, and projections until 2035: findings from the Global Burden of Disease Study 2021 - Niping Qin; Yangyan Fan; Tao Yang; Zhiping Yang; Daiming Fan (Biomarker Research)
Abstract Background and objective Gastric cancer (GC) remains a significant global health challenge, characterized by high incidence and mortality rates, particularly in East Asia. A comprehensive understanding of the disease burden of gastric cancer is crucial for developing effective prevention and treatment strategies. However, comprehensive global assessments of the disease burden of gastric cancer remain limited. This study, based on the Global Burden of Disease (GBD) framework, systematically analyzes global trends in gastric cancer from 1990 to 2021 and projects future trends through 2035, aiming to provide scientific evidence for policymaking. Methods The data were derived from the Global Burden of Disease (GBD) Study 2021, covering gastric cancer (GC) incidence, mortality, disability-adjusted life years (DALYs), age-standardized incidence rates (ASIRs), age-standardized death rates (ASDRs), and age-standardized DALY rates (ASRs) across 204 countries and regions from 1990 to 2021. The Bayesian age-period-cohort model was employed to project trends up to 2035. Results In comparison with 1990, both the incidence and mortality of GC rose in 2021, with over 1.23 million new cases recorded globally, resulting in 954,373.60 deaths and 22,786,633.10 DALYs. Between 1990 and 2021, the ASIRs, ASDRs, and ASRs decreased by 42% (ranging from 49 to 35%), 49% (ranging from 55 to 43%), and 53% (ranging from 58 to 47%), respectively. The peak ASIRs and ASDRs in 2021 were seen in the high-middle SDI quintile. Males exhibited higher rates of ASDRs, ASIRs, and ASRs compared to females. In 2021, East Asia and high-income North America bore the largest burden of smoking-related GC, while Central Europe experienced the highest burden from high-sodium diets. Forecasts toward 2035 indicate a continued decline in both ASIRs and ASDRs. Conclusions Despite notable reductions in both incidence and mortality, GC remains a substantial global burden, affecting various regions and countries. Deaths and DALYs related to high-sodium diets and smoking have shown an overall decline. However, substantial regional and age-related disparities persist. Targeted interventions, such as smoking control and promoting the intake of fresh fruits and vegetables, are essential in diminishing GC risk.